Long-legged flies (Diptera: Empidoidea: Dolichopodidae) from the Balkan Mountains, Bulgaria, with first records for the Balkan Peninsula - Mihail Kechev; Blagoy Koychev (Historia naturalis bulgarica, 2021)
The paper presents information about 35 dolichopodid flies collected from 12 localities in the Balkan Mountains at the territory of Bulgaria. Two species, Campsicnemus pusillus and Sciapus maritimus, are recorded for the first time in Bulgaria and on the Balkan Peninsula. Another nine ones are listed for the first time to the Balkan Mountains range.